An improved design of microwave biosensor for measurement of tissues moisture - Jilani, M.T. (Institute of Electrical and Electronics Engineers Inc., 2015)
In this contribution, a simple but highly sensitive biosensor based on microstrip ring-resonator is presented for tissues moisture evaluation. By incorporating high impedance ring, tight and enhanced coupling mechanism the proposed 1 GHz ring-resonator demonstrates significant change in the resonance frequency than normal resonator. Simulated and measured results are in good agreement. The proposed resonator gives 37 better performance than the conventional resonator. Â© 2014 IEEE.